Satellite Images Fusion Using Mapped Wavelet Transform Through PCA - Abduljabbar, Hameed Majeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper a new fusion method is proposed to fuse multiple satellite images that are acquired through different electromagnetic spectrum ranges to produce a single gray scale image. The proposed method based on desecrate wavelet transform using pyramid and packet bases, the fusion process preformed using two different fusion rules, where the low frequency part is remapped through the use of PCA analysis basing on covariance matrix and correlation matrix, and the high frequency part is fused using different fusion rules (adding, selecting the higher, replacement), then the restored image is obtained by applying the inverse desecrate wavelet transform. The experimental results show the validity of the proposed fusion method to fuse such images with equally representation comparing with the general wavelet fusion method that fuses the high frequency parts only.